Angiotensin regulation of amygdala response to threat in high-trait-anxiety individuals - Reinecke, A; Browning, M; Breteler, J; Kappelmann, N; Ressler, KJ; Harmer, CJ; Craske, MG (Elsevier, 2018)
Background The antihypertensive drug losartan has been shown to improve memory in humans as well as learning and fear extinction in rodent models, highlighting its potential to have similar synergistic effects on exposure-based cognitive behavioral therapy for anxiety disorders. This study investigated the effect of losartan on neural correlates of processing threat versus safety stimuli in highly anxious individuals to identify potential pathways of how the drug might facilitate psychological treatment. Methods Thirty healthy volunteers high in trait anxiety were randomly assigned to a single dose of losartan (50 mg) versus placebo before undergoing functional magnetic resonance imaging. We measured brain response to happy and fearful faces presented for 80 seconds to assess emotional processing and habituation over time. Results The placebo group showed similarly high left amygdala activation early on during presentation of fearful and happy faces, which decreased over time. In contrast, losartan reduced amygdala response to happy faces early on. In response to fearful faces, the drug prevented habituation, caused sustained amygdala activation, and led to increased activation in other brain areas associated with threat processing, such as the insula and putamen. Conclusions Our findings suggest two distinct effects of losartan on emotional processing, including an improvement of early discrimination of stimuli as threatening versus safe, and facilitation of threat processing. Both processes are known to be relevant for successful exposure, highlighting two potential pathways by which losartan might exert facilitative effects on psychological treatment.